Effect of ACE inhibitors on the course of SARS-CoV-2 in a patient with pre-existing chronic kidney disease: a clinical case - Zavalna, I.M. (KIDNEYS, 2023)
The presence of in combination with hypertension stage 1–2 and its medical correction using renin-angiotensin-aldosterone system (RAAS) inhibitors significantly affects the health of patients who are infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). SARS-CoV-2 uses RAAS as a tool to penetrate the cell, namely the receptor of angiotensin-converting enzyme (ACE) 2. The purpose of the work: to assess the dynamics of clinical and laboratory indicators in a patient with SARS-CoV-2-associated nephropathy against the background of taking ACE inhibitors. This article describes a clinical case from the author’s own practice. Timely prescription of etiotropic therapy for coronavirus disease 19 significantly reduces complications of chronic kidney disease course with hypertension.